Umar bin Khattab's Governance: a Paradigm of Intellectual Renewal - Alamshah, Anisah; Syukur, Syamzan; Rahmawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Umar ibn Khattab, one of the illustrious four rightly guided caliphs, is celebrated not only for his legendary tales of valor and unyielding determination but also for his imposing character. His reputation in this regard often eclipses the recognition of his impactful political endeavors on the Muslim community. This modest research endeavor seeks to unveil the innovations and pioneering ideas introduced by Umar al-Faruq, which encompass a wide spectrum of political, economic, and socio-communal ijtihad (independent reasoning). Employing a qualitative research methodology, the study draws upon primary sources, including hadiths and the wisdom of the Prophet's companions, historical texts, and supplements this with secondary sources like scholarly journals, articles, and preceding research works. The amassed data will be meticulously dissected and presented descriptively. The research unearths Umar's audacious overhaul of existing systems while steadfastly upholding the principles delineated in the Quran and the Prophetic tradition. His reforms resulted in the evolution of modern ijtihad, the codification of the Quran, the eradication of land ownership by non-indigenous landlords, and a comprehensive metamorphosis of the defense mechanisms within the Islamic caliphate. These far-reaching reforms have left an enduring impact on the development of the Muslim community, with their reverberations still palpable in contemporary times. Keywords: umar ibn khattab, caliphs, ijtihad, intelectual renewal, governance